Prevalence of acute kidney injury following percutaneous nephrolithotomy - Saina Paymannejad; Mehdi Dehghani; Razieh Jafari Dehkordi; Shahram Taheri; Farid Shamlou; Hanieh Salehi; Reza Kazemi (Journal of Research in Medical Sciences, 2024)
Background: The objective is to evaluate the prevalence of acute kidney injury (AKI) as an early complication of the percutaneous nephrolithotomy (PCNL) procedure. Materials and Methods: From May 2022 to October 2022, we conducted a retrospective study on patients undergoing PCNL procedures in two of the tertiary medical centers affiliated with Isfahan University of Medical Sciences. Patients’ baseline characteristics, laboratory values, perioperative data, and stone features were documented. AKI was defined either as a ≥0.3 mg/dL increase in the serum creatinine level within 2 days, or a ≥1.5-fold increase in baseline serum creatinine level within 7 days after the operation. Laboratory values were measured 1 day before PCNL and daily thereafter until discharge. Patients were followed 1 week later to detect all of the possible cases of AKI. Results: The final analysis was performed on 347 individuals. AKI developed in 16 (4.61%) cases. The two groups were comparable regarding age (P = 0.887), gender (P = 0.566), and underlying comorbidities including diabetes mellitus (P = 0.577) and hypertension (P = 0.383). The mean body mass index (BMI) (P < 0.001) and both frequency and severity of hydronephrosis (P < 0.001) were significantly different. A higher mean PCNL duration (P < 0.001), period of hospitalization (P < 0.001), and blood loss volume (P < 0.001) were observed in those who developed AKI. Overall, 56.3% (9) of patients in the AKI group and 2.7% (9) in the non-AKI group required the establishment of more than one access tract, during the procedure (P < 0.001). A lower preoperative hemoglobin level was observed in the AKI group (P < 0.001). Those with AKI had significantly larger stones (3.08 ± 0.46 vs. 2.41 ± 0.23 cm, P < 0.001) and higher Hounsfield units (P < 0.001). In addition, in the AKI group, most of the calculi (81.3%, 13) were of staghorn type, whereas in the non-AKI group, calculi were most frequently located in the middle calyx (30.2%, 100), (P < 0.001). Conclusion: The prevalence of post-PCNL AKI is approximately 4.61%. The mean BMI, preoperative hemoglobin level, PCNL duration, intraoperative blood loss volume, and hospitalization period were significantly higher among patients who developed AKI. Those with AKI had significantly larger stones with higher Hounsfield units and more frequently of staghorn type. The two groups were not statistically different regarding age, gender, and presence of comorbidities (hypertension and diabetes mellitus).